Comparison of the intestinal mucosal microbiota in dogs diagnosed with idiopathic inflammatory bowel disease and dogs with food-responsive diarrhea before and after treatment. Issue 2 (6th December 2017) - Kalenyak, Katja; Isaiah, Anitha; Heilmann, Romy M; Suchodolski, Jan S; Burgener, Iwan A
Abstract: We report the first study to evaluate the intestinal mucosal microbiota of dogs with inflammatory bowel disease (IBD) and dogs with food-responsive diarrhea (FRD) before and after treatment. It was hypothesized that differences in the microbial composition exist between both disease groups and within groups pre- vs. post-treatment. Duodenal and colonic biopsies were obtained endoscopically from 24 dogs (15 FRD, 9 IBD) before and after treatment. The intestinal microbiota was evaluated by Illumina sequencing of the bacterial 16S rRNA gene. The global bacterial composition did not differ between IBD and FRD dogs, nor between treatment status. However, several bacterial taxa showed a difference in abundance. Comparing disease groups, an unclassified genus of Neisseriaceae was abundant in the duodenum in the IBD group, whereas Bilophila occurred more frequently in the duodenum and Burkholderia in the colon of FRD dogs. Comparing the microbiota pre- and post-treatment revealed Enterococcus, Corynebacterium and Proteobacteria to be enriched in the duodenum of FRD dogs pre-treatment, while Bacteroides was abundant in the colon post-treatment. In dogs with IBD, Bacteroides also reached significant abundance in the colon post-treatment. In conclusion, some differences in individual bacterial taxa were identified between IBD and FRD dogs and between treatment status. Abstract : This is the first study to evaluate the intestinal mucosal microbiota of dogs with idiopathic inflammatory bowel disease and dogs with food-responsive diarrhea before and after treatment.